Criminal Law Description of Domestic Violence - Saparovna, Niyozova Salomat; Allanova, Azizakhon; Khamidov, Nurmukhammad; Sunnatov, Vokhid; Toshev, Otabek; Gazibekov, Khurshid (Journal of Ecohumanism, 2025)
This article analyzes issues related to the criminal-legal description of domestic violence. Also, in this article, criminal-legal and criminological literature is analyzed about the criminological description, causes, conditions, nature, social and signs of different concepts of violence and violence in the family, and the author expressed his thoughts on this matter. This article focuses on the physical and mental, sexual and economic types of criminal violence in the family, revealing their different aspects.